Resonant nanostructures for highly confined and ultra-sensitive surface phonon-polaritons - Alexander M. Dubrovkin (Nature Portfolio, 2020)
Here, the authors demonstrate tunable highly confined surface phonon-polaritons in CMOS-compatible interfaces of nm-thick germanium on silicon carbide. The sensitivity of real-space polaritonic patterns is a pathway for the detection of the interface composition change at sub-nanometer level.